Computer Network Management Using a Mikrotik Router at the Immigration Office Class I TPI Bengkulu City - Al-Hidayat Jambak; Hari Aspriyono; Abdussalam Al Akbar (Jurnal Media Computer Science, 2022)
The Bengkulu City Immigration Office Class I TPI Bengkulu City, located in Bengkulu City, on Jl. Development of number 23 Padang Harapan Bengkulu. The problems that occur in the office lie in the network that is not well organized, the internet connection is slow, and the network is less secure because it only uses Wired Equivalent Privacy (WEP) as security protection in the network, and Bandwidth is not evenly distributed throughout each computer. . Based on the results of discussions that have been carried out with the immigration office and immigration IT (data attached). then to solve the problems described above, at the immigration office it is necessary to create an alternative that is used to solve the problem, namely making a network management system that is more secure and regular in bandwidth usage, using a proxy as a router, and bandwidth management management using load balancing techniques. with the PCC (Peer Connection Classifier) method The application of bandwidth management using load balancing techniques at the Bengkulu City TPI class I immigration office was successfully carried out because it distributed traffic loads on two or more ISP (Internet service provider) connection lines. With the implementation of bandwidth management, it can help distribute bandwidth evenly throughout the Client PC. Based on the tests conducted at the Immigration Office Class I TPI Bengkulu city, it can be concluded that the implementation of bandwidth management has been successful, where PC Clients can access the internet evenly, and the use of internet access is more scheduled during working hours, rest hours, and outside working hours.